Exploring motivators and challenges for preceptors to teach in the clinical settings: a survey-based study - Nooran Badeeb; Yara Alsolami; Miad Alhamrani; Fadi Hassanin; Waseem Aalam (BMC Medical Education)
Abstract Background The retention of qualified faculty in medical colleges is hindered by low salaries and inadequate faculty-to-student ratios, despite intrinsic motivators like job satisfaction playing a critical role in faculty motivation. This study aims to understand and address the specific motivating factors and constraints within Saudi Arabia's medical education sector. Methodology A cross-sectional, validated online survey was conducted from November 2023 to January 2024 among physicians in Saudi Arabia's governmental and private sectors. Participants ranked teaching motivators and challenges using a Likert scale ranging from 5 (very important) to 1 (not very important). The collected data were analyzed using descriptive statistics and Chi-square test. Results Of the 145 respondents, 62.1% were male, with a mean age of 38.2 years (SD = 8.9). Saudi nationals comprised 54.5% of the sample. Sharing knowledge (64%) and educating the next generation (63%) were the top motivators. Notably, student preparedness was crucial for 45.5%. In contrast, extrinsic factors like financial gain (20%) and recognition events (9.7%) ranked lowest. The main challenges were heavy clinical workload (31.3%) and lack of time (28%). Conclusion Preceptors were primarily motivated by intrinsic factors, with student preparedness being the most significant external factor. Time constraints and clinical workload were the major challenges to teaching. These insights can guide strategies to better support clinical educators.